Ataxia–telangiectasia patients presenting with hyper-IgM syndrome. Issue 6 (17th February 2009) - Noordzij, J G; Wulffraat, N M; Haraldsson, Á; Meyts, I; Veer, L J van't; Hogervorst, F B L; Warris, A; Weemaes, C M R
Abstract : Ataxia–telangiectasia (A–T) is characterised by progressive neurological abnormalities, oculocutaneous telangiectasias and immunodeficiency (decreased serum IgG subclass and/or IgA levels and lymphopenia). However, 10% of A–T patients present with decreased serum IgG and IgA with normal or raised IgM levels. As cerebellar ataxia and oculocutaneous telangiectasias are not present at very young age, these patients are often erroneously diagnosed as hyper IgM syndrome (HIGM). Eight patients with A–T, showing serum Ig levels suggestive of HIGM on first presentation, are described. All had decreased numbers of T lymphocytes, unusual in HIGM. The diagnosis A–T was confirmed by raised α-fetoprotein levels in all patients. To prevent mistaking A–T patients for HIGM it is proposed to add DNA repair disorders as a possible cause of HIGM.